Clinical and Economic Comparison of Ceftaroline Fosamil (CPT) and Daptomycin (DAP) for Methicillin-Resistant Staphylococcus aureus (MRSA) Bloodstream Infections (BSI). (4th October 2017) - Zasowski, Evan J; Trinh, Trang D; Claeys, Kimberly; Lagnf, Abdalhamid M; Klinker, Kenneth; Estrada, Sandy; Davis, Susan L; Huang, Vanthida; Potoski, Brian A; Levine, Donald; Kaye, Keith S; Bonine, Nicole; et al.
Abstract: Background: DAP is the primary alternative to vancomycin for MRSA BSI but other options are needed in cases of treatment failure and/or reduced susceptibility. Observational data suggest CPT may be effective but comparative data are limited. This study compares the outcomes and hospital cost of MRSA BSI treated with DAP or CPT. Methods: A multicenter retrospective cohort study of patients age ≥ 18 years with MRSA BSI treated with ≥ 72 hours of CPT or DAP from 2011 – 2016. Patients with a pneumonia source, BSI clearance prior to study drug, ≥ 96 hours of prior MRSA-active therapy, and those receiving ≥ 24 hours of concomitant MRSA-active therapy during first 96 hours study drug were excluded. CPT and DAP patients were propensity score matched using variable match ratio on Charlson comorbidity index, APACHE II score, and BSI source. The primary outcome was composite failure defined as 30-day mortality, BSI duration ≥ 7 days post-study drug initiation, or 60-day recurrence. Secondary outcomes included composite components and hospital cost post-BSI onset. Following bivariate analysis, conditional logistic regression was used to assess the association between treatment group and composite failure while controlling for confounders. Results: 99 patients (27 CPT, 72 DAP) were matched. No statistically significant differences in characteristics were observed between treatment groups. Common BSI sources in CPT and DAP groups, respectively, were bone/joint (48.1 vs.. 41.7%), endocarditis (22.2 vs. 37.5%), skin/soft tissue (18.5 vs. 18.1%), intravenous catheter (11.1 vs. 12.1%). Outcomes of interest are listed in table below. Adjusting for peripheral vascular disease and diabetes, treatment group was not associated with composite treatment failure (adjusted odds ratio CPT 0.823, 95% CI 0.31 – 2.15). Conclusion: No difference in outcomes or hospital cost was observed. These data are preliminary and should be interpreted with caution due retrospective nature of the study. Disclosures: K. Klinker, The Medicines Company: Scientific Advisor, Consulting fee; S. L. Davis, Allergan: Grant Investigator and Scientific Advisor, Consulting fee and Research grant; Merck: Grant Investigator and Scientific Advisor, Consulting fee and Research grant; K. S. Kaye, Allergan: Consultant, Consulting fee; Merck: Consultant and Grant Investigator, Consulting fee and Research support; N. Bonine, Allergan: Employee, Salary; P. Gillard, Allergan: Employee, Salary; M. J. Rybak, Allergen: Scientific Advisor, Consulting fee